The Footprints of Poly-Autoimmunity: Evidence for Common Biological Factors Involved in Multiple Sclerosis and Hashimoto’s Thyroiditis - Perga, Simona; Martire, Serena; Montarolo, Francesca; Giordani, Ilaria; Spadaro, Michela; Bono, Gabriele; Corvisieri, Stefania; Messuti, Ilaria; Panzica, Giancarlo; Orlandi, Fabio; Bertolotto, Antonio (Frontiers in Immunology, 2018)
Autoimmune diseases are a diverse group of chronic disorders and affect a multitude of organs and systems. However, the existence of common pathophysiological mechanisms is hypothesized and reports of shared risk are emerging as well. In this regard, patients with multiple sclerosis (MS) have been shown to have an increased susceptibility to develop chronic autoimmune thyroid diseases, in particular Hashimoto's thyroiditis (HT), suggesting an autoimmune predisposition. However, studies comparing such different pathologies of autoimmune origin are still missing till date. In the present study, we sought to investigate mechanisms which may lead to the frequent coexistence of MS and HT by analyzing several factors related to the pathogenesis of MS and HT in patients affected by one or both diseases, as well as in healthy donors. In particular, we analyzed PBMC gene expression levels of common candidate genes such as TNFAIP3, NR4A family, BACH2, FOXP3 and PDCD5, in addition to the Treg percentage and the 25-OH vitamin D serum levels. Our findings support the plausibility of the existence of common deregulated mechanisms shared by MS and HT, such as BACH2/PDCD5-FOXP3 pathways and Tregs. Although the biological implications of these data need to be further investigated, we have highlighted the relevance of studies comparing different autoimmune pathologies for the understanding of the core concepts of autoimmunity.